Partisipasi Masyarakat Dalam Pembangunan Infrastruktur Di Desa Romanglasa Kecamatan Bontonompo Kabupaten Gowa - Riskayanti, Riskayanti; Setiawati, Budi; Mone, Ansyari (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2022)
This study aimed to find out thecommunity participation in infrastructure development in the village of Romanglasa, Bontonompo District, Gowa Regency. This study used a qualitative research by explaining the events that occurred in the field during the research. There were 11 informants consisting of the Romanglasa village head, Romanglasa village secretary, 2 BPD members, 1 hamlet head member, 1 RT member, 1 RW member, 1 NGO member and 3 community members. This data collection used  observation, interviews and documentation with informants. The results of this study showed that community participation in infrastructure development in Romanglasa Village, Bontonompo District, Gowa Regency in the form of thought participation was still very minimal seen from how the community did not participate in the planning and decision-making process because the government did not give a big chance the community to be involved in problem formulation so that people were apathy towards infrastructure development in the planning process of Musrembang and RPJMDes, participation of personnel in the form of mutual assistance and community service, participation of expertise in the form of community-owned skills, participation of goods in the form of tools and equipment that could be used to assist infrastructure development work, participation of money in the form of funds or procedure.Keywords: community participation, infrastructure development